HIV Progression Perturbs the Balance of the Cell-Mediated and Anti-Inflammatory Adaptive and Innate Mycobacterial Immune Response - Andrew R. DiNardo; Anna M. Mandalakas; Gugu Maphalala; Godwin Mtetwa; Temhlanga Mndzebele; Piluca Ustero; Makhosazana Hlatshwayo; Emily M. Mace; Jordan S. Orange; George Makedonas (Mediators of Inflammation)
Introduction. Our objective is to understand how HIV infection increases the risk of progression from latent tuberculosis (TB) to active disease. We understand now that immunity is a balance of competing immune responses by multiple cell types. Since T-lymphocyte production of interferon-gamma (IFN-γ) in response to Mycobacterium tuberculosis (Mtb) antigens fails to differentiate disease from latent infection, we applied a comprehensive profiling methodology to define immune biomarkers that reliably predict a patient’s TB risk. Methods. We established a cohort of HIV-infected adults with TB disease from Swaziland. Multiparametric flow cytometry was used to quantify the mycobacterial-specific anti-inflammatory (IL-4 and IL-10) and proinflammatory (IFN-γ) immune response. Results. From 12 HIV-infected Swaziland patients with TB disease, the CD4+, CD8+, Double Negative, and CD56+CD3− lymphocytes increase their IL-4 : IFN-γ ratio as HIV disease worsens (Spearman r of −0.59; −0.59; −0.60; and −0.59, resp.; p<0.05). Similarly, HIV severity is associated with an increased IL-10 : IFN-γ ratio (Spearman r of −0.76; p=0.01). Conclusion. As HIV disease progresses, both the adaptive and innate branches skew away from an inflammatory and towards anti-inflammatory phenotype.